The results of the study relationship to the territorial brand of «Big Yalta» as a tourist resort - E. V. Dianina (Путеводитель предпринимателя)
Results of the empirical research of resort’s «Big Yalta» state and its perception by tourists and citizens are represented in the article. Based on the research findings, the program of this resort’s promotion is brought out and the recommendations for its further development are given. The purpose of this article is to identify the resort’s problems and development prospects to change its image perception among target audience. The article used general scientific methods: analysis, synthesis, online survey, association method.